(untitled) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Tripartiella; Tripartiella bulbosa; T. bursiformis; T copiosa; T. nana; T. obtusa; T. tilapiae; Ciliophora; Trichodinidae Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 49-55